The Paradigm of Sexual Violence Against Women in Indonesia: Between Causes and Solutions - Edi Sutikno; Eugenia Brandao Da Silva (Jurnal Ilmiah Dunia Hukum, 2025)
This study examines sexual harassment against women in Indonesia as a structural manifestation deeply rooted in social, cultural, and institutional inequality rather than as an isolated phenomenon. Using a qualitative-descriptive approach through literature review and socio-legal analysis, this research identifies key factors that perpetuate sexual violence, including the surplus of male power within patriarchal structures, victim blaming practices, the lack of sexual and gender awareness education, stigma surrounding reporting, and the objectification of women in the media. These interrelated factors not only reflect the symbolic domination of men over women’s bodies and spaces but also highlight the state’s and society’s failure to establish a comprehensive and just protection system. The findings reveal that addressing sexual harassment requires cross-sectoral, holistic, and sustainable interventions. Progressive legal reforms such as the implementation of the Sexual Violence Crime Law (UU TPKS) must be accompanied by comprehensive, gender-based sexual education, victim-centered law enforcement, and strengthened media ethics in reporting violence. Accordingly, the study recommends that the government enhance the implementation of UU TPKS by improving the capacity of law enforcement officers, expanding integrated protection services across regions, and incorporating comprehensive sexual education into the national curriculum. Society must actively reject the normalization of violence and eliminate stigma against victims, while civil society organizations, educational institutions, and the media should strengthen collaboration to promote awareness, victim-oriented policies, and ethical reporting practices. The synergy among these sectors is crucial to building an inclusive, just, and sustainable system to eradicate sexual harassment against women in Indonesia.